CATHETER-RELATED BLOODSTREAM INFECTION AMONG HEMODIALYSIS PATIENTS: INCIDENCE AND MICROBIOLOGICAL PROFILE - Nuradeen, Bryar E.; Omer, Sherko A.; Sharif, Dana A.; Othman, Tara S. (Journal of Sulaimani Medical College, 2018)
Background Catheter-related bloodstream infections are the most serious infection complication among hemodialysis patients. Objectives To identify the incidence of catheter-related bloodstream infections among hemodialysis patients in Sulaimani city. Also to find the relationship of infection with the catheter type, site, and duration, and to identify the causative organisms and their antimicrobial susceptibility. Methods A cross-sectional observational study done in hemodialysis patients suspected to have catheter-related bloodstream infections. Two blood samples (from peripheral vein and catheter lumen) were cultured aerobically on blood culture media. Removed catheters were also cultured aerobically to detect catheter colonization. Isolates were identified based on cultural characteristic, microscopy, biochemical profile and Vitek® 2 system. Antimicrobial susceptibilities test done using Kirby-Bauer method. Results A total 117 patients suspected to have catheter-related bloodstream infections were included from two dialysis centers (49 from Shar center and 68 from Qirga center). These patients experienced 164 suspected infection episodes, of these, 146 (89%) yielded bacterial growth giving infection incidence of 24.95 per 1000 dialysis-sessions through different catheters. Coagulase-negative staphylococci were the commonest isolates in both centers, 51.5% and 19.3% in Shar and Qirga center respectively followed by S. aureus (25.7%) in Shar and pseudomonas spp. (15.8%) in Qirga center. Catheter colonization was caused by coagulase-negative staphylococci (39.1%) in Shar and Pseudomonas spp. (23.3%) in Qirga. Linezolid, tigecycline and teicoplanin were most effective against most gram-positive bacteria. Likewise, ampicillin-sulbactam and piperacillin-tazobactam were effective against most of the gram-negative isolates. None of the empirically used antibiotics, vancomycin and gentamicin, was fully effective against all the isolates. Conclusions Incidence of catheter-related bloodstream infections is high in Sulaimani dialysis centers. The dialysis centers revealed different isolates but mainly staphylococci and pseudomonas spp. Prolong empirical antimicrobial use is not recommended and such infections should be treated according to the antimicrobial susceptibility results. Infection was less with permanent tunneled catheters compared to temporary catheters, however, temporary hemodialysis catheter inserted to internal jugular vein showed less chance of infection than in subclavian and femoral vein catheters.
Keywords: Hemodialysis; Central venous catheters; Catheter-related bloodstream infection; Sulaimani